2015
DOI: 10.1186/s12887-015-0426-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition practice, compliance to guidelines and postnatal growth in moderately premature babies: the NUTRIQUAL French survey

Abstract: BackgroundThe nutritional care provided to moderately premature babies is poorly studied. For a large cohort of such babies, we aimed to describe: nutrition practice intentions, comparison of the intended with the actual practice, compliance of actual practice to current nutrition guidelines, and postnatal growth.MethodsA questionnaire was sent out to 29 neonatal intensive care units in France, in order to address practice intentions. In the same units, retrospective patient’s data were collected to assess act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 21 publications
3
31
3
1
Order By: Relevance
“…Different NICUs have different nutrition support practices . In our study, the average maximum doses of protein intake in EUGR and non‐EUGR groups were 3.15 ± 0.48 and 2.98 ± 0.42 g/kg/d, respectively, and were lower than the recommended levels (3.5–4.0 g/kg/d).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Different NICUs have different nutrition support practices . In our study, the average maximum doses of protein intake in EUGR and non‐EUGR groups were 3.15 ± 0.48 and 2.98 ± 0.42 g/kg/d, respectively, and were lower than the recommended levels (3.5–4.0 g/kg/d).…”
Section: Discussioncontrasting
confidence: 53%
“…It is important to provide stable and adequate nutrients not only in the first weeks of life, but throughout the hospital, and even when discharged home. The implementation of a program with potential improvement of nutrition practices may promote a more adequate supply of nutrients, reduce EUGR, and decrease comorbidities in VLBWIs …”
Section: Discussionmentioning
confidence: 99%
“…Research that evaluates the growth of premature infants uses the concept of “delta z score” to capture a decline or deceleration in WAz 77 , 78 . For example, a delta z score of 0 (or within a small range of 0) could reflect normal growth along or near a growth trajectory; a positive delta z score would reflect accelerated growth; and a negative delta z score would reflect a deceleration in growth.…”
Section: Using the Indicators In Clinical Practicementioning
confidence: 99%
“…Unfortunately, we still fail to implement these strategies sufficiently, as recently highlighted in a French survey [9]. Using a questionnaire on 276 preterm (30–33 weeks gestational age) neonates hospitalized in 29 different NICUs, the authors documented that there was divergence between the intended and the actual practice for both protein and lipid intake.…”
Section: Do We Practice What We Know?mentioning
confidence: 99%
“…The authors concluded that nutritional support was not in compliance with recommendations and that the rate of EUGR remained relevant. Efforts are needed to improve adherence to nutrition guidelines and growth outcomes: implementation remains a major hurdle [9]: no time to waste . …”
Section: Do We Practice What We Know?mentioning
confidence: 99%